2017
DOI: 10.1111/ijlh.12746
|View full text |Cite
|
Sign up to set email alerts
|

Osmotic gradient ektacytometry: A valuable screening test for hereditary spherocytosis and other red blood cell membrane disorders

Abstract: Introduction: New generation osmotic gradient ektacytometry has become a powerful

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
58
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(62 citation statements)
references
References 38 publications
3
58
0
Order By: Relevance
“…RBC deformability at normoxic conditions is compromised in patients with SCD due to irreversibly sickled cells, as well as altered hydration causing a decrease in surface/volume ratio . Osmotic gradient ektacytometry, in which deformability is measured as a function of a continuous change in osmolarity, is a well‐established method, in particular in hereditary disorders of the red cell membrane . In SCD, osmotic gradient ektacytometry showed that increasing HbF induces a better surface‐to‐volume ratio thereby improving deformability in untransfused patients with SCD .…”
Section: Introductionmentioning
confidence: 99%
“…RBC deformability at normoxic conditions is compromised in patients with SCD due to irreversibly sickled cells, as well as altered hydration causing a decrease in surface/volume ratio . Osmotic gradient ektacytometry, in which deformability is measured as a function of a continuous change in osmolarity, is a well‐established method, in particular in hereditary disorders of the red cell membrane . In SCD, osmotic gradient ektacytometry showed that increasing HbF induces a better surface‐to‐volume ratio thereby improving deformability in untransfused patients with SCD .…”
Section: Introductionmentioning
confidence: 99%
“…A case in point is ektacytometry, which is a powerful tool for the diagnosis of DHS1. However, the co‐inheritance of conditions, such as beta‐thalassemia trait and splenectomy, may modify the ektacytometry curve shape thereby leading to a misdiagnosis (Da Costa et al , ; Lazarova et al , ; Huisjes et al , ; Zaninoni et al , ; Llaudet‐Planas et al , ). The flow‐cytometric osmotic fragility test is a new method for the diagnosis of HS, HE and DHS in combination with eosin‐5'‐maleimide testing.…”
Section: New Insights Into the Diagnosis Of Red Cell Membrane Disordersmentioning
confidence: 99%
“…The diagnosis of HS is based on the triad: (1) anaemia with jaundice, (2) severe splenomegaly and (3) spherocytosis, easily demonstrated by the peripheral blood morphological examination ( Figure 5). Currently the diagnosis of HS can be easily performed by measuring RBC deformability and osmotic gradient ektacytometry (OGE) using the new generation LoRRca Osmoscan from Mechatronics [27]. Curves obtained with this device allow a clear distinction between hereditary spherocytosis and the other RBC hereditary membranopathies, elliptocytosis and xerocytosis ( Figure 6).…”
Section: Membranopathiesmentioning
confidence: 99%